Thermodynamics of Clouding Behaviour of Polyoxyethylene-(20)- cetyl Ether (Brij-58) with Glycine and Serine - BHADANE, B.S.; PATIL, T.J. (Asian Journal of Chemistry, 2010)
The phenomenon of solubilization of non-ionic surfactant polyoxyethylene( 20)cetyl ether (Brij-58) have been studied through the influence of additives such as amino acids i.e., glycine and serine in aqueous medium by measuring the cloud points of the pure surfactant and with glycine (Gly) and serine (Ser). The cloud point of pure surfactant found to be decreased with increased [Bj-58]. The cloud point of mixed system also shows same trends with increased [Gly] and [Ser]. This is mainly due to increased micelle concentrations. The influence of amino acids on the cloud point of Brij-58 is a clear indication that the phenomenon of clouding is associated with the different micelles coalescing. The phase separation results from micelle-micelle interaction. Considering cloud point as threshold temperature of the solubility. The thermodynamic parameters of clouding process (ΔGºCl , ΔHºCl and ΔSºCl ) have been evaluated using ‘Phase Separation Model’. It is found that the overall clouding process is exothermic and ΔHºCl > TΔSºCl indicating that the process of clouding is guided by both enthalpy and entropy. This work support the conjecture that the clouding is critical phenomenon rather than the growth of micelles. The findings of the present work supports the probable evidence of macromolecule-surfactant interactions in aqueous medium.